Assigning exposure to pesticides and solvents from self-reports collected by a computer assisted personal interview and expert assessment of job codes: the UK Adult Brain Tumour Study. Issue 4 (23rd March 2006) - Hepworth, S J; Bolton, A; Parslow, R C; van Tongeren, M; Muir, K R; McKinney, P A
Abstract : Objectives: To compare assignment of occupational pesticide and solvent exposure using self-reported data collected by a computer assisted personal interview (CAPI) with exposure based on expert assessment of job codes. To discuss the advantages and disadvantages of using a CAPI to collect individual occupational exposure data. Methods: Between 2001 and 2004, 1495 participants were interviewed using a CAPI for a case-control study of adult brain tumours and acoustic neuromas. Two types of occupational data were collected: (1) a full history, including job title from which a job code was assigned from the Standard Occupational Classification; and (2) specific details on pesticide and solvent exposure reported by participants. Study members' experiences of using the CAPI were recorded and advantages and disadvantages summarised. Results: Of 7192 jobs recorded, the prevalence of self-reported exposure was 1.3% for pesticides and 11.5% for solvents. Comparing this with exposure expertly assessed from job titles showed 53.6% and 45.8% concordance for pesticides and solvents respectively. Advantages of the CAPI include no data entry stage, automatic input validation, and a reduction in interviewer bias. Disadvantages include an adverse effect on study implementation as a consequence of resources required for programming and difficulties encountered with data management prior to analysis. Conclusions: Different methods of exposure assessment derive different exposure levels for pesticide and solvent exposure at work. Agreement between self-reported and expert assessment of exposure was greater for pesticides compared to solvents. The advantages of using a CAPI for the collection of complex data outweigh the disadvantages for interviewers and data quality but using such a method requires extra resources at the study outset.